Following Nithi’s Thought: Zomia, Tai People, and a New Version of History - Pawakapan, Niti (Journal of Social Sciences Naresuan University, 2026)
This article presents the core arguments based on Nidhi Eoseewong’s ideas on Thai and Lanna histories, motivations of Nidhi’s interests in exploring the concept of Zomia, his conceptual proposals of the Zomia introduced by James C. Scott and other scholars, including related data and academic works, with the aim of featuring the Zomia, people, and the historical development that has occurred in this particular region. According to the survey, several studies on Zomia, including Nidhi’s works, indicate that Zomia, a vast area that includes Thailand, is rich in various natural resources, diverse inhabitants, and their socio-cultural patterns. This condition resulted in the dynamics of political and economic structures and multilayered trading. Thus, with the objective of writing a new version or “unconventional” Thai history that follows Nidhi’s ideas, this article’s author sees the necessity of making sense of the complex Zomia, which impacted the people living in this area.